Child Development three to five [videorecording] - Conrad, Tim; Finzen, Susan (Meridian Education Corporation, 1990)
Overviews the major physical, emotional, and intellectual stages of development for children from three to five years old. Included are interviews with a child psychologist and parents. Also included is an exploration of how children at this stage become self-aware and begin socialization.